2022
DOI: 10.1371/journal.pone.0270146
|View full text |Cite
|
Sign up to set email alerts
|

Towards developing a beef meat export oriented policy in Tanzania: -Exploring the factors that influence beef meat exports-

Abstract: The purpose of this study was to investigate the factors that influence beef meat exports in Tanzania, with a particular focus on the years 1985 to 2020, in enhancing the development of beef meat export-oriented policy in Tanzania, thereby enhancing beef exports in Tanzania. A time-series panel dataset was analyzed using both descriptive statistics and ordinary least squares (OLS) linear regression analyses models. As per the descriptive analyses, beef meat exports reached the highest pick of 4,300 tons per ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, China's WTO membership, the 'Belt and Road' Initiative, and the common borders had a positive significant impact on its exports of pork. Kibona et al (2022) investigated the factors that influence beef exports in Tanzania. Econometric results of the study revealed that terms of trade, Tanzania GDP per capita, global beef meat consumption, trade openness, and beef outputs positively and significantly affecting beef exports in Tanzania.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, China's WTO membership, the 'Belt and Road' Initiative, and the common borders had a positive significant impact on its exports of pork. Kibona et al (2022) investigated the factors that influence beef exports in Tanzania. Econometric results of the study revealed that terms of trade, Tanzania GDP per capita, global beef meat consumption, trade openness, and beef outputs positively and significantly affecting beef exports in Tanzania.…”
Section: Literature Reviewmentioning
confidence: 99%